Classification of Circular Mass of Breast Cancer Using Artificial Neural Network Vs Discriminant Analysis in Medical Image Processing - حمد، كارزان فيدهي; سيليك، بولنت; أحمد، رزكار مغديد (جامعة الموصل - كلية علوم الحاسوب والرياضيات, 2024)
في السنوات الأخيرة، كان هناك زيادة ملحوظة في الاهتمام بتقنيات التصنيف الذكية المتجذرة في التعلم الآلي في مجال العلوم الطبية. على وجه التحديد، تم استخدام التعلم الآلي، وهو مجال محوري للذكاء الاصطناعي، على نطاق واسع لمساعدة المهنيين الطبيين في التنبؤ بالأمراض المختلفة وتشخيصها. تطبق هذه الدراسة خوارزميتين متميزتين للتعلم الآلي لمعالجة مشكلة التشخيص الطبي المتعلقة بالكتل الدائرية في سرطان الثدي. تشمل مجموعة البيانات 150 حالة من مرضى سرطان الثدي. الهدف الأساسي هو تقييم ومقارنة فعالية الشبكات العصبية الاصطناعية (أنس) والتحليل التمييزي الخطي (لدا) المصنفات على أساس المعايير الرئيسية: الدقة والحساسية والنوعية، ومعامل كابا في التنبؤ الجماهير الدائرية داخل سرطان الثدي. تشير النتائج إلى أن أداء المصنف أن يفوق أداء نموذج لدا، وتحقيق دقة %97.7، وحساسية 95%، وخصوصية 100 %، ومعامل كابا 95.31% بالإضافة إلى ذلك، تكشف النماذج النهائية المجهزة عن العوامل المحورية التي تؤثر بشكل كبير على الكتل الدائرية في سرطان الثدي، مما يسلط الضوء على الصلابة والإنتروبيا باعتبارها المتغيرات الأكثر أهمية. In recent years, there has been a notable increase in interest regarding intelligent classification techniques rooted in Machine Learning within the domain of medical science. Specifically, machine learning, a pivotal area of artificial intelligence, has been extensively utilized to aid medical professionals in predicting and diagnosing various diseases. This study applies two distinct machine learning algorithms to address a medical diagnosis concern related to circular masses in breast cancer. The dataset encompasses 150 cases of breast cancer patients. The primary objective is to assess and compare the effectiveness of artificial neural networks (ANNs) and linear discriminant analysis (LDA) classifiers based on key criteria: accuracy, sensitivity, specificity, and the kappa coefficient in predicting circular masses within breast cancer. Results indicate that the performance of the ANN classifier surpasses that of the LDA model, achieving an accuracy of 97.7%, sensitivity of 95%, specificity of 100%, and a kappa coefficient of 95.31%. Additionally, the final fitted models unveil the pivotal factors significantly influencing circular masses in breast cancer, highlighting Solidity and Entropy as the most critical variables.
Keywords: الذكاء الاصطناعي -- التشخيص الطبي -- شرطان الثدي -- الصور الطبية